Brand Management - Pollák, František; Markovič, Peter (IntechOpen, 2022)
Brand Management discusses several issues of marketing management within the limits of marketing communication. Chapters address such topics as Internet marketing, the transition from offline to online in the process of building brand equity, standardization versus adaptation of brand elements in international markets, and "living" the brand.